Crescimento, produção e qualidade de melancia em função de diferentes doses de nitrogênio na savana de Roraima - Barros, Márcio Mesquita (2011)
The cultivation of watermelon in Roraima is growing every year due to favorable climate conditions, however, fertilization with nitrogen, which can interfere with the production and fruit quality has not been studied. The objective was to evaluate the effect of different nitrogen doses application on the agronomic performance and quality of watermelon cv. Crimson Sweet. This research was conducted in the field conditions at Universidade Federal de Roraima, Boa Vista, RR, from January to April 2010. The experimental design was randomized blocks with four replications. The treatments consisted of five nitrogen doses (50, 100, 150, 200 and 250 kg ha-1) applied as urea in a conventional manner. The results showed that commercial production of fruits increased to 40,428 kg ha-1, using 144.7 kg ha-1 of N. The quality of watermelon was influenced by the treatments. The pH was not influenced by treatments and averaged 5.34. The length to diameter ratio and shell thickness also were not affected by treatments, while the firmness of the fruit content of soluble solids (TSS), acidity (TA), sugar content (reducing, non reducing and total), the ascorbic acid and TSS / TA were affected by the nitrogen doses.